Mass gatherings in Italy: a study from the 2015 Milan Expo - Pietro Marino; Enzo Albergoni; Aida Andreassi; Gianluca Chiodini; Lucia Colombi; Cristina Corbetta; Gabriella Nucera; Marco Salmoiraghi; Alberto Zoli (Journal of Health and Social Sciences)
Introduction. A mass gathering (MG) is when a large number of people come together in a particular location for a specific purpose. Expo 2015 was an universal exposition hosted by Milan, Italy. The Pre-Hospital Emergency Company (AREU) of Lombardy Region (Milan-Italy) was involved in planning and managing the emergency rescue response inside the Expo 2015 area in Milan. In this paper, we review the AREU medical and public health response for the 2015 Milan Expo. Methods. Existing risk-assessment processes for MGs were used (the Arbon Predictive Score and Maurer Score) to define the expected resources and the impact on the health systems. The objective of the plan was to reduce the impact of the event by adopting the model of First Aid Points (advanced medical posts) deployed in the event site acting as ‘first health filters’ for the hospital network in Milan. Results. Our data indicate that 13,579 visitors were rescued in the ‘Red Area’ from 1 May to 31 October (with an average of 73 cases per day); 9,501 of them needed initial treatment or observation time at the First Aid Points, 1,289 of them were hospitalised (1% Red code, 29% Yellow code, 70% Green code); 65% of patients (57% female, with a mean age of 37 years old) had medical problems. Fatigue, light- headedness, dizziness, syncope, loss of consciousness and headache were the prevalent medical diagnoses. Conclusions. Our study confirms that environmental factors, such as the weather, can contribute to large numbers of ill people at MGs. Overall, the AREU of Lombardy Region demonstrated excellent preparation for the Expo 2015 MG. Flexibility, integration and strong cooperation between the pre-hospital settings and hospitals were incorporated into the application of the plan. The final data showed the effectiveness of the adopted model and the reduced impact on the hospital network.